Performance of vermicomposted wastes for tomato (Lycopersicon Esculentum Mill.), production: A case study of Embu, Kenya - Miriam Mochache; Rebecca Yegon; Onesmus Ngetich (International Journal of Recycling of Organic Waste in Agriculture, 2021)
Purpose To investigate the effect of vermicomposted kitchen, market and tea wastes on tomato growth and yield and assess the benefits and costs that arise.Method A field experiment arranged in the randomized complete block design with five experimental treatments: vermicomposted kitchen, market, tea wastes, NPK fertilizer and a control, replicated thrice was conducted. Data were collected on plant height, number of leaves, number of branches, number of flower stalks, fruit number, fruit weight, above-ground biomass, marketable tomato yield, soil nutrient content, pH, texture and exchangeable acidity. Data obtained were analyzed using SAS version 9.4 by subjecting to one-way Analysis of Variance (ANOVA). Biophysical crop data means were separated using Tukey’s Studentized Range (HSD) test at p=0.05 significance level. T-test was used to determine the difference in soil nutrient content (Nitrogen (N), Phosphorus (P), Potassium (K), Carbon (C)) at the beginning and end of the study. The benefits and costs were analyzed using the benefit-cost ratio formula.Results The three vermicomposts had a similar effect (p>0.05) in influencing most of the tomato crop variables such as plant height, leaves number, branch number and flower stalks number. Tea waste vermicompost and kitchen waste vermicompost gave significantly high tomato yields of 115 t ha-1 and 113 t ha-1 at p=0.0001 as well as the highest benefit-cost ratio of 1.4:1.Conclusion Tea, market and kitchen wastes have a potential for use in the production of high-quality vermicompost that can be used as a soil amendment to enhance tomato performance.